The rights to copyright in light of the matter 03- 05 and their protection - Boughloute, Nabil (Journal of Human Sciences, 2023)
The law came to protect the rights entrusted to persons because of this protection’s importance at the domestic and international level. Like other rights, intellectual rights came with a special regulation and a special law that protects the owners of this category from the infringements that befell them, especially in light of the spread of the means of imitation and piracy. Regulate copyright on his literary and artistic work as a means to rebuke the infringers of these important rights in the advancement and development of peoples.